Connections in a Liminal Space - Vig, Leanne D. (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2025)
This reflective paper is both a partial response to Dr. Julie Rattray’s opening keynote presentation, Travels in a Liminal Space: The Need for Guardians and Guides in SoTL, at the 2023 symposium, and an account of my journey to connection and revitalization through the Scholarship of Teaching and Learning (SoTL). After burning out mid-career, I found myself struggling with my identity, not only as an academic but also outside of work. I was at a crossroads heading into the last decade or so of my career. In this reflection, I will explore SoTL identity, threshold concepts, and liminal spaces from my perspective as an instructor and educational developer in the college and polytechnic sector.